2023
DOI: 10.1186/s12890-023-02436-1
|View full text |Cite
|
Sign up to set email alerts
|

COPD exacerbations and patient-reported outcomes according to post-bronchodilator FEV1 – a post-hoc analysis of pooled data

Abstract: Background Management strategies of chronic obstructive pulmonary disease (COPD) need to be tailored to the forced expiratory volume in one second (FEV1), exacerbations, and patient-reported outcomes (PROs) of individual patients. In this study, we analyzed the association and correlation between the FEV1, exacerbations, and PROs of patients with stable COPD. Methods This was a post-hoc analysis of pooled data from two cross-sectional studies that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 55 publications
(63 reference statements)
3
8
0
Order By: Relevance
“…Upon further analysis of the differences in demographic characteristics according to severity, we found that age was significantly lower in the moderate, severe, and very severe groups. This finding is consistent with that of a previous international study that analyzed demographic char-acteristics based on FEV 1 in patients with COPD [13], which also reported that patients in the very severe group tended to be younger. However, this observation differs from that of another study that examined the general characteristics of patients with COPD in the Korean National Health and Nutrition Examination Survey [1] and found that higher severity was associated with older age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Upon further analysis of the differences in demographic characteristics according to severity, we found that age was significantly lower in the moderate, severe, and very severe groups. This finding is consistent with that of a previous international study that analyzed demographic char-acteristics based on FEV 1 in patients with COPD [13], which also reported that patients in the very severe group tended to be younger. However, this observation differs from that of another study that examined the general characteristics of patients with COPD in the Korean National Health and Nutrition Examination Survey [1] and found that higher severity was associated with older age.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, greater physical disability and psychological stress are linked to a poorer quality of life and less favorable long-term prognosis [11,12]. These findings un-derscore the importance of considering a comprehensive picture that includes patient-reported outcomes and psychological indicators when assessing patients with COPD and determining appropriate therapeutic approaches [13]. Relying solely on a single metric such as disease severity may not provide a complete understanding of a patient's condition.…”
Section: Introductionmentioning
confidence: 99%
“…International Journal of Chronic Obstructive Pulmonary Disease 2024:19 1132 from 0 (no frailty) to 25 (severe frailty), and the frailty status of the participants was classified as robust (0-3), pre-frail (4-7), or frail (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). 37 Notably, the BMI score was calculated using values obtained from measurements taken at the same time as the pulmonary function test, rather than self-reported.…”
Section: Dovepressmentioning
confidence: 99%
“…These results were supported by those from research groups in Beijing and the UK, the latter by Hanlon et al using data from the UK Biobank. 14,16,17 Although there are several factors that have been reported as predictors of acute exacerbations in subjects with COPD, including severity of airflow limitation, [21][22][23][24] COPD-specific health status measured by patient-reported outcomes (PROs) such as the COPD Assessment Test (CAT), [25][26][27][28][29] symptoms of chronic bronchitis, 30 blood eosinophilia 31 and a history of exacerbations that may reflect an independent susceptibility phenotype, 24 the severity of airflow limitation or FEV 1 may be the most common characteristic of patients who subsequently develop acute exacerbations, especially from the standpoint of COPD patient care. This study sought to answer the following research questions:…”
Section: Introductionmentioning
confidence: 99%
“…The results from a 6MWT and Forced Expiratory Volume in one second [FEV1] have been found not to be directly comparable, as several factors affect the performance in the 6MWT [18]. The same applies to associations between MRC-score and FEV1 [19][20][21]. FEV1 is an objective and well-validated measure of pulmonary function in patients with COPD, although the measurement includes possible sources of error [22][23][24] The primary aim of this systematic review is therefore to investigate whether there is an association between lung function impairment de ned as FEV1 in relation to expected value and anxiety or depression in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%